STRATEGI PEMENANGAN PASANGAN CALON ANIES BASWEDAN DAN SANDIAGA UNO DALAM PEMILIHAN GUBERNUR DAN WAKIL GUBERNUR DKI JAKARTA TAHUN 2017 - Widya, Arya Parama; Sardini, Nur Hidayat (Journal of Politic and Government Studies, 2019)
Election of Regional Heads or Pilkada is a manifestation of popular sovereignty to elect local leaders in the region. DKI Jakarta Province has become one of the regions that held the 2017 simultaneous regional election. Its status as the national capital has made the results of the DKI Jakarta Pilkada a barometer of national politics. In the 2017 DKI Jakarta Pilkada, Anies Baswedan and Sandiaga Uno won the contest and defeated the incumbent with a big voice. In fact, the Anies and Sandi couples managed to wipe out 5 administrative regions and 1 district throughout the DKI Jakarta Province. Interestingly, Anies and Sandi managed to defeat the incumbent with a high level of public satisfaction supported by the government party.The results of the study show that the factors that influence the victory of Anies and Passwords are several things. These factors are grouped into general factors and special factors. The general factor in Anies and Sandi's victory was the existence of resistance to incumbents, the emergence of money politics, and the cooperation of volunteers and cadres of good political parties. Whereas the special factor that underlies the victory is the emergence of identity politics in the campaign period and the issue of reclamation which is opposed by couples Anies and Sandi.Keywords: local election, identity politics, marketing politics